Analisis Manajemen Risiko Pada Usaha Peternakan Ayam Broiler Abdul Jalil Rangkuti Di Desa Aek Marian Kabupaten Mandailing Natal - Muhamad Alfi Sahrin Ramadan Rangkuti; Andy Hakim; Sari Fitri (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
This livestock business is capable of producing thousands of chickens per harvest with a 30–35-day rearing cycle. However, the farm faces various risks, particularly related to fluctuating chicken mortality rates from the DOC period to harvest. The main contributing factors are suboptimal cage conditions, extreme weather, and chicken stress. The objective was to analyze the various risks that affect broiler chicken productivity. This study used a descriptive qualitative approach through observation, interviews, and document review. The results identified six types of risks. Three risks are categorized as high, namely poor cage hygiene, chicken mortality that can spread viruses, and uneven chicken growth. Two risks are categorized as medium, namely disturbances from predators and extreme weather. Meanwhile, one risk is categorized as low, namely unpleasant odor. This study is expected to serve as a reference in minimizing livestock risks. Recommendations provided include maintaining cage cleanliness regularly, providing balanced nutritional feed, improving biosecurity systems, and anticipating extreme weather and pest animals. By implementing these strategies, it is hoped that livestock productivity can increase and risks can be minimized.